Resistin as a Systemic Inflammation-Related Biomarker for Sarcopenia in Patients With Chronic Obstructive Pulmonary Disease - Gao, Jinghan; Deng, Mingming; Li, Yanxia; Yin, Yan; Zhou, Xiaoming; Zhang, Qin; Hou, Gang (Frontiers in Nutrition, 2022)
Background: Sarcopenia is common in patients with chronic obstructive pulmonary disease (COPD) and is mainly caused by systemic inflammation. Resistin acts as a proinflammatory cytokine and is involved in the activation of multiple inflammatory signaling pathways. The aim of this study was to determine the relationship between resistin levels and systemic inflammation and to assess the clinical value of circulating resistin for sarcopenia in patients with COPD. Methods: In this prospective observational study, we enrolled 235 patients with COPD who were divided into development and validation sets. The definition of sarcopenia followed the guidelines from the Asian Working Group for Sarcopenia. Serum concentrations of resistin and TNF-α were measured using an enzyme-linked immunosorbent assay (ELISA). Results: In this study, higher serum resistin levels were significantly associated with lower skeletal muscle mass and muscular strength. The serum resistin levels in patients with sarcopenia were significantly higher than those in patients without sarcopenia. The serum resistin level had positive correlations with the serum TNF-α level (r = 0.250, p = 0.007). The predictive efficacy of the serum resistin level (AUC: 0.828) for sarcopenia was superior to that of the serum TNF-α level (AUC: 0.621). The cutoff point (7.138 ng/ml) for the serum resistin level was validated in the validation set (AUC: 0.818). Conclusions: Serum resistin levels were associated with systemic inflammation and can be used accurately and easily to predict sarcopenia in patients with COPD.